2005
DOI: 10.1194/jlr.m400438-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol increases HDL-C levels in humans

Abstract: Studies have shown that phosphatidylinositol (PI) can stimulate reverse cholesterol transport by enhancing the flux of cholesterol into HDL and by promoting the transport of high density lipoprotein-cholesterol (HDL-C) to the liver and bile. The goal of this study was to determine the safety and therapeutic value of PI after oral administration to normolipidemic human subjects. We performed a randomized 2 week study in 16 normolipidemic subjects. Subjects received either 2.8 or 5.6 g of PI, with or without foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 26 publications
1
54
1
1
Order By: Relevance
“…114 In a small clinical trial, 2 weeks of treatment with oral phosphatidylinositol resulted in a significant increase of 13% to 18% in HDL-C levels. 115 Another group reported that oral administration of the phospholipid 1,2-dimyristoyl-sn-glycero-3-phosphocholine to apoE-null mice led to an increase in HDL-C levels and HDL function and a reduction in atherosclerosis. 116 One appeal of phospholipids as therapeutic agents is that they are natural substances and would be expected to have a good safety profile.…”
Section: Therapies Intended To Alter Hdl and Apoa-i Metabolism To Raimentioning
confidence: 99%
“…114 In a small clinical trial, 2 weeks of treatment with oral phosphatidylinositol resulted in a significant increase of 13% to 18% in HDL-C levels. 115 Another group reported that oral administration of the phospholipid 1,2-dimyristoyl-sn-glycero-3-phosphocholine to apoE-null mice led to an increase in HDL-C levels and HDL function and a reduction in atherosclerosis. 116 One appeal of phospholipids as therapeutic agents is that they are natural substances and would be expected to have a good safety profile.…”
Section: Therapies Intended To Alter Hdl and Apoa-i Metabolism To Raimentioning
confidence: 99%
“…Intravenous administration of PI has also been shown to inhibit lecithin-cholesterol acyltransferase (LCAT) and cholesterylester transfer protein (CETP), two important enzymes involved in cholesterol metabolism (36,37). Inhibition of these enzymes by anionic phospholipids results in the inhibition of production, transfer and storage of cholesterol in the apoB-containing lipoprotein pool (32,38). Anionic phospholipids such as PI and PG may also regulate triglyceride metabolism by stimulation of triglyceride lipases including hepatic-, lipoprotein-and pancreatic lipase.…”
Section: Cytotoxicity Assaysmentioning
confidence: 98%
“…Polar lipids are considered health-promoting bioactive constituents in the human diet due to their effect on plasma lipid profile, colon cancer pathogenesis and even gut bacteria population (Dillehay et al, 1994;Burgess et al, 2005). The concentrations of polar lipids in milk also have industrial implications due to their emulsifying properties, which are required for some food systems (Thompson and Singh, 2006).…”
Section: Introductionmentioning
confidence: 99%